ELR(+) chemokine signaling in host defense and disease in a viral model of central nervous system disease - Hosking, Martin P.; Lane, Thomas E. (Frontiers in Cellular Neuroscience, 2014)
Intracranial infection of the neurotropic JHM strain of mouse hepatitis virus (JHMV) into the central nervous system (CNS) of susceptible strains of mice results in an acute encephalomyelitis, accompanied by viral replication in glial cells and robust infiltration of virus-specific T cells that contribute to host defense through cytokine secretion and cytolytic activity. Mice surviving the acute stage of disease develop an immune-mediated demyelinating disease, characterized by viral persistence in white matter tracts and a chronic neuroinflammatory response dominated by T cells and macrophages. Chemokines and their corresponding chemokine receptors are dynamically expressed throughout viral infection of the CNS, influencing neuroinflammation by regulating immune cell infltration and glial biology. This review is focused upon the pleiotropic chemokine receptor CXCR2 and its effects upon neutrophils and oligodendrocytes during JHMV infection and a number of other models of CNS inflammation.